Sport jak narkotyk. Uzależnienie behawioralne wśród osób aktywnych fizycznie. = Sport like a drug. Behavioral addiction among physically active people - Gęga, Katarzyna; Szkoda, Lawia; Jachacz-Łopata, Małgorzata (Journal of Education, Health and Sport, 2016)
Gęga Katarzyna, Szkoda Lawia, Jachacz-Łopata Małgorzata. Sport jak narkotyk. Uzależnienie behawioralne wśród osób aktywnych fizycznie = Sport like a drug. Behavioral addiction among physically active people. Journal of Education, Health and Sport. 2016;6(7):187-194. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.57322 http://ojs.ukw.edu.pl/index.php/johs/article/view/3669 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.06.2016. Revised 09.07.2016. Accepted: 09.07.2016. Sport jak narkotyk. Uzależnienie behawioralne wśród osób aktywnych fizycznie Sport like a drug. Behavioral addiction among physically active people Katarzyna Gęga1, Lawia Szkoda1, Małgorzata Jachacz-Łopata2 1Studenckie Koło Naukowe przy Zakładzie Medycyny Fizykalnej, Katedra Fizjoterapii, Wydział Nauk o Zdrowiu, Śląski Uniwersytet Medyczny w Katowicach 2Zakład Medycyny Fizykalnej, Katedra Fizjoterapii, Wydział Nauk o Zdrowiu, Śląski Uniwersytet Medyczny w Katowicach Autorzy: Katarzyna Gęga1, Lawia Szkoda1, dr n. med. Małgorzata Jachacz-Łopata2 1 Studenckie Koło Naukowe przy Zakładzie Medycyny Fizykalnej, Katedra Fizjoterapii, Wydział Nauk o Zdrowiu, Śląski Uniwersytet Medyczny w Katowicach 2Zakład Medycyny Fizykalnej, Katedra Fizjoterapii, Wydział Nauk o Zdrowiu, Śląski Uniwersytet Medyczny w Katowicach Streszczenie: Uzależnienia behawioralne to uzależnienia, w których substancje chemiczne nie odgrywają żadnej roli. Ich przedmiotem są zachowania i działania akceptowane społecznie. Zdarza się, że aktywność fizyczna zajmuje centralne miejsce w życiu człowieka i zaczyna przysłaniać inne sfery takie jak życie zawodowe, rodzinne, czy kontakty towarzyskie. Brak kontroli, uczucie wewnętrznego przymusu czy efekt odstawienia to tylko niektóre z przesłanek, które mogą świadczyć o uzależnieniu od sportu. Słowa kluczowe: aktywność fizyczna, uzależnienia behawioralne, profilaktyka uzależnień. Summary: In behavioral addictions chemicals do not play any role. They relate to behavior and actions socially acceptable. It happens that physical activity occupies a central place in human life and begins to overshadow other aspects of life such as professional, family or social contacts. Lack of control, a feeling of compulsion or withdrawal effects are just some of the conditions that may indicate addiction to the sport. Key words: physical activity, behavioral addiction, exercise addiction, addictions preventing.